A new candidate quasar strongly lensed by the galaxy cluster WHJ0400-27 with an 18″ image separation - Bazzanini, Lorenzo; Angora, G.; Scialpi, M.; Rosa, G. Di; Bergamini, P.; Rosati, P.; Lombardi, M.; Abriola, D.; Acebron, A.; D’Addona, M.; Granata, G.; Grillo, C.; et al. (Astronomy and astrophysics, 2025)
Context. Time-delay cosmography (TDC) using quasi-stellar objects (QSOs) multiply lensed by galaxies has recently emerged as an independent and competitive tool for measuring the value of the Hubble constant. Lens galaxy clusters hosting multiply imaged QSOs, when coupled with an accurate and precise knowledge of their total mass distribution, are equally powerful cosmological probes. However, fewer than ten such systems have been identified to date. Aims. Our study aims to expand the limited sample of cluster-lensed QSO systems by identifying new candidates within rich galaxy clusters. Methods. We started with a sample of approximately 10 5 galaxy cluster candidates from Dark Energy Survey and Wide-field Infrared Survey Explorer imaging data, along with a pure catalogue of over one million QSOs from Gaia DR3. We cross-correlated these datasets to identify lensed QSO candidates near the cores of massive galaxy clusters. Results. Our search detected three lensed double candidates across an area of ≈5000 sq degree. In this work, we focus on the best candidate - a double QSO with a Gaia-based redshift of 1.35, projected behind the moderately rich cluster WHJ0400-27 at z phot = 0.65. Based on a first spectroscopic follow-up study, we confirm the two QSOs at z = 1.345 with indistinguishable spectra, and a brightest cluster galaxy at z = 0.626. These observations support the strong lensing nature of this system, though some tension arises when the cluster mass from the preliminary lens model is compared to other mass proxies. We also considered whether such a system could be a rare physical association of two distinct QSOs separated by a projected physical distance of ≈150 kpc. If further spectroscopic observations confirm its lensing nature, such a rare lens system would exhibit one of the largest image separations observed to date (Δϑ = 17.8″) and would enable interesting TDC applications.